A judicialização da mediação no poder judiciário brasileiro: mais do mesmo nas disputas familiares? - Cristiana Vianna Veras; Roberto Fragale Filho (e-cadernos ces)
The text begins by distinguishing between mediation and conciliation as constitutive means of the conflict, pointing out their main differences from the role that the figure of the third party (mediator and conciliator) plays in these institutes. Next, we identify initiatives towards the legislation of mediation, in order to sketch out the movement for the normative institutionalization of mediation within the Brazilian judiciary. Finally, taking into account the peculiaritie s inherent to mediation as a means of settlement other than the conciliation and adjudication models, we present some reflections on how the practices of mediation can be developed in the field of legal disputes relating to family conflicts.